Extraction and Stability Test of Anthocyanin from Buni Fruits (Antidesma Bunius L) as an Alternative Natural and Safe Food Colorants - Amalia, Fera; Afnani, Galih Nur (Fakultas Farmasi, Universitas Gadjah Mada, 2013)
Synthetic dyes have widely been usedin food products. However, the safety issues regarding the use of synthetic dyes arise. Buni (Antidesma bunius) which contains anthocyanins can be an alternative of synthetic dyes. Anthocyanins are red, blue, or violet natural colorants from many types of plants. The aim of the study was to determine the best extraction process and to evaluate the stability of anthocyanins extracted from the Buni fruits. Different combinations of the solvents namely aquadest, ethanol, hydrocloride acid, and citric acid were used to extract the anthocyanins. The most appropriate combination of solvent was determined by the analysis of total anthocyanins content and color intensity using UV-Visible spectrophotometer. The stability of anthocyanins was evaluated using different pH values and temperature. Ethanol at 70% and citric acid at 3% was the most appropriate combination for the extraction with the highest total concentration of anthocyanin (0.58%) and color intensity (0.324). The stability of the anthocyanins from Buni was affected by the value of pH, which the most stable condition was set at pH values of 4-5.